archaeopar asitology - Mosab Nouraldein Mohammed Hamad (جامعة الشيخ عبدالله البدري, 2018)
Archaeoparasitology, a multi-disciplinary field within paleopathology, is the study of parasites in archaeological contexts. It includes studies of the protozoan and metazoan parasites of humans in the past, as well as parasites which may have affected past human societies, such as those infesting domesticated animals. Reinhard suggested that the term "archaeoparasitology" be applied to "... all parasitological remains excavated from archaeological contexts ... derived from human activity" and that "the term Paleoparasitology be applied to studies of nonhuman, paleontological material." Paleoparasitology includes all studies of ancient parasites outside of archaeological contexts, such as those found in amber and even dinosaur parasites. The first archaeoparasitology report described calcified eggs of Bilharzia haematobia (now Schistosoma haematobium) from the kidneys of an ancient Egyptian mummy. Since then, many fundamental archaeological questions have been answered by integrating our knowledge of the hosts, life cycles and basic biology of parasites, with the archaeological, anthropological and historical contexts in which they are found.